Evaluasi dan Perbaikan Desain Antarmuka Pengguna Menggunakan Pendekatan Human-Centered Design (HCD) (Studi Kasus: Djarum Beasiswa Plus) - Ainun Nuril Laily; Retno Indah Rokhmawati; Admaja Dwi Herlambang (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
From the result of survey, 32 of 47 scholarship applicant and awardee respondents said that Djarum Beasiswa Plus's (DBP) website has an icon that is not clear and respondents admitted the difficulty in achieving their goals. This research focus on evaluating and improving DBP's website by involving users. The method that involves the user in developing system is Human-Centered Design (HCD). HCD is an approach to interactive systems development that aims to make systems usable and useful by involving users. This research will discuss about evaluating and improving user interface DBP's website by context of use, user requirements, making solution design and evaluating solution design. Design evaluation uses usability testing to assess aspects of effectiveness, efficiency, and user satisfaction. The evaluation was conducted by five respondents on the tasks scenario sheet. This research showed that the solution design after applied HCD has a higher value of usability. On the aspect of effectiveness, the success rate is 100%. On the aspect of efficiency, the avarage time of the solution design is much faster, from 29.49 seconds to 06.30 seconds. On the aspect of user satisfaction, all respondents said prefer to choose the interface of the solution design because it provides more ease in achieving goals.